Neuroprotective effect from stem bark extracts of Knema laurina against H₂O₂- and Aβ(1-42)-induced cell death in human SH-SY5Y cells - Ismail, Norsharina; Akhtar, Muhammad Nadeem; Ismail, Maznah; Zareen, Seema; Shah, Syed Adnan Ali; Lajis, Nordin; Tajuddin, Saiful Nizam (Taylor & Francis, 2015)
The stem bark extracts of Knema laurina inhibited the hydrogen peroxide (H2O2)- and aggregated amyloid β-peptide 1–42 length (Aβ1–42)-induced cell death in differentiated SH-SY5Y cells. Exposure of 250 μM H2O2 or 20 μM Aβ1–42 to the cells for 24 h reduced 50% of cell viability. Pretreatment of cells with ethyl acetate extract (EAE) or n-butanol extract (BE) at 300 μg/mL and then exposure to H2O2 protected the cells against the neurotoxic effects of H2O2. Besides, methanolic extract (ME) at 1 and 10 μg/mL exerted neuroprotective effect on Aβ1–42-induced toxicity to the cells. These results showed that EAE, BE and ME exhibited neuroprotective activities against H2O2- and Aβ1–42-induced cell death. Flavonoids (3–6) and β-sitosterol glucoside (8) were isolated from the EAE. Compound 1 was isolated from hexane extract, and compounds 2 and 7 were isolated from dichloromethane extract. All these observations provide the possible evidence for contribution in the neuroprotective effects.